Combined effects of solar UV radiation and CO2-induced seawater acidification on photosynthetic carbon fixation of phytoplankton assemblages in the South China Sea - Wu, Y. P.; Gao, K. S.; 高坤山 (2010)
National Basic Research Program of China [2009CB421207]; Ministry of Education of China for Key Project [308015]; National Natural Science Foundation of China [40930846, 40876058] We carried out short term pCO(2)/pH perturbation experiments in the coastal waters of the South China Sea to evaluate the combined effects of seawater acidification (low pH/high pCO(2)) and solar UV radiation (UVR, 280-400 nm) on photosynthetic carbon fixation of phytoplankton assemblages. Under photosynthetically active radiation (PAR) alone treatments, reduced pCO(2) (190 ppmv) with increased pH resulted in a significant decrease in the photosynthetic carbon fixation rate (about 23%), while enriched pCO(2) (700 ppmv) with lowered pH had no significant effect on the photosynthetic performance compared to the ambient level. The apparent photosynthetic efficiency decreased under the reduced pCO(2) level, probably due to C-limitation as well as energy being diverged for up-regulation of carbon concentrating mechanisms (CCMs). In the presence of UVR, both UV-A and UV-B caused photosynthetic inhibition, though UV-A appeared to enhance the photosynthetic efficiency under lower PAR levels. UV-B caused less inhibition of photosynthesis under the reduced pCO(2) level, probably because of its contribution to the inorganic carbon (Ci)-acquisition processes. Under the seawater acidification conditions (enriched pCO(2)), both UV-A and UV-B reduced the photosynthetic carbon fixation to higher extents compared to the ambient pCO(2) conditions. We conclude that solar UV and seawater acidification could synergistically inhibit photosynthesis.